Technical Efficiency in the Decentralized Care of the Developmentally Disabled - Dusansky, Richard; Wilson, Paul W. (The Review of Economics and Statistics, 1994)
This paper analyzes the technical efficiency of group home care for the developmentally disabled in the Detroit metropolitan area. Linear programming methods are used to construct a production frontier that allows measurement of relative technical efficiency among homes in the sample. A sensitivity analysis is performed to identify influential observations in the data that might result from measurement error that could distort the efficiency measures. A regression analysis is undertaken to examine the effect of various factors on measured efficiency. Policy implications are discussed in the concluding section. Copyright 1994 by MIT Press.